Synchronous Primary Malignancies: Incidental Detection of Ascending Colon Adenocarcinoma During Staging of Invasive Ductal Carcinoma of the Breast - Salif Balde; Ulrich Igor Mbessoh Kengne; Jaafar Ibn Abou Talib Thiam; Joël Gabin Konlack Mekontso; Sokhna Diop Niang; Amacoumba Fall; Mamadou Ndiaye; Gorgui Sarr; Etienne Tossou Zoure; Mamadou Sow; Sidy Ka (Case Reports in Oncological Medicine)
Multiple primary malignant neoplasms (MPMNs) are defined as two or more distinct tumors in the same individual. Synchronous breast and colon cancers are infrequent and present management challenges due to the lack of standardized guidelines. We report a 73-year-old woman presenting with a right breast mass, subsequently diagnosed as Grade 2 invasive ductal carcinoma. Staging CT incidentally revealed right colon wall thickening, and colonoscopy with biopsy confirmed moderately differentiated invasive adenocarcinoma. Following neoadjuvant chemotherapy, she underwent simultaneous radical mastectomy with axillary lymph node dissection and right hemicolectomy. Postoperative recovery was uneventful. Adjuvant chemoradiation was administered per multidisciplinary team (MDT) recommendation. Synchronous breast and colon cancers pose unique diagnostic and treatment planning challenges. MDT collaboration is crucial for personalized treatment strategies and optimized outcomes in these complex cases.